2019
DOI: 10.1111/fme.12403
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying contributions to tournament catches among resident, stocked and hybrid black basses (Micropterus spp.)

Abstract: Millions of Florida bass, Micropterus floridanus Lesueur, are stocked annually into populations of largemouth bass, Micropterus salmoides Lacepède, to increase trophy fish abundance. However, little effort has related the role that resultant hybrids make to angler catches. Largemouth bass were sampled from an important recreational fishery subject to extensive Florida bass stocking to address the hypothesis that anglers capture Florida bass, largemouth bass and hybrids at rates equivalent to their overall abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…2019), no differences have been observed between the proportion of FX‐LMB and LMB in the population and the proportion of these fish captured by tournament anglers (Hargrove et al. 2020). Similarly, Lutz‐Carrillo and Dumont (2012) noted no differences in angler catch rates and electrofishing catch rates of LMB hybrids and LMB in Texas reservoirs, although FLB angler catch was lower than electrofishing capture in some reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2019), no differences have been observed between the proportion of FX‐LMB and LMB in the population and the proportion of these fish captured by tournament anglers (Hargrove et al. 2020). Similarly, Lutz‐Carrillo and Dumont (2012) noted no differences in angler catch rates and electrofishing catch rates of LMB hybrids and LMB in Texas reservoirs, although FLB angler catch was lower than electrofishing capture in some reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…Catchability has been demonstrated to be lower for FLB than for LMB in a pond setting (Kleinsasser et al 1990). However, in Chickamauga Reservoir, Tennessee, which has been stocked with FLB for many years and contains large numbers of FX-LMB and LMB (Hargrove et al 2019), no differences have been observed between the proportion of FX-LMB and LMB in the population and the proportion of these fish captured by tournament anglers (Hargrove et al 2020). Similarly, Lutz-Carrillo and Dumont (2012) noted no differences in angler catch rates and electrofishing catch rates of LMB hybrids and LMB in Texas reservoirs, although FLB angler catch was lower than electrofishing capture in some reservoirs.…”
Section: Differences Between Largemouth Bass and Backcrossesmentioning
confidence: 99%
See 2 more Smart Citations